Computers and Information Technology as a Source of Learning Media for Elementary School Teachers - Monalia, Monalia; Asfiyanti, Nurul Aini; Putri, Syafia Eka (International Journal of Natural Science and Engineering, 2021)
The increasingly rapid development of computers and information technology at this time provides benefits and conveniences for teachers and students. It is hoped that the development of computers and information technology can stimulate thoughts, provoke activity, feelings, and attention of students so that the learning process goes well and student and teacher communication runs smoothly. This study aims to determine the development of ICT as a source of learning media. This research is qualitative descriptive research. This type of research is literature review research reviewed from journals taken from e-journals and Google Scholar. The data collection technique used in this research is reading the journals obtained and noting the things needed in this journal. The data validation technique used in this journal is using data source triangulation techniques. Based on the study results, it can be concluded that learning to use computers and information technology has many benefits that can be taken. Make it easier for teachers and students to convey and receive the learning they want to convey. With this ICT, teachers can also do e-learning so that students are more independent with flexible time.